Molecular Characterization of Maize Acetylcholinesterase. A Novel Enzyme Family in the Plant Kingdom - Sagane, Yoshimasa (American Society of Plant Biologists, 2005)
Acetylcholinesterase (AChE) has been increasingly recognized in plants by indirect evidence of its activity. Here, we report purification and cloning of AChE from maize (Zea mays), thus providing to our knowledge the first direct evidence of the AChE molecule in plants. AChE was identified as a mixture of disulfide- and noncovalently linked 88-kD homodimers consisting of 42- to 44-kD polypeptides. The AChE hydrolyzed acetylthiocholine and propyonylthiocholine, but not S-butyrylthiocholine, and the AChE-specific inhibitor neostigmine bromide competitively inhibited its activity, implying that maize AChE functions in a similar manner as the animal enzyme. However, kinetic analyses indicated that maize AChE showed a lower affinity to substrates and inhibitors than animal AChE. The full-length cDNA of maize AChE gene is 1,471 nucleotides, which encode a protein having 394 residues, including a signal peptide. The deduced amino acid sequence exhibited no apparent similarity with that of the animal enzyme, although the catalytic triad was the same as in the animal AChE. In silico screening indicated that maize AChE homologs are widely distributed in plants but not in animals. These findings lead us to propose that the AChE family, as found here, comprises a novel family of the enzymes that is specifically distributed in the plant kingdom.